The Effect of Providing Incentives, Task Complexity, and Internal Control on Employee Performance - Andi Azzah Fauziyyah; Alimuddin Alimuddin (Hasanuddin Economics and Business Review, 2023)
A successful company is influenced by several internal factors, one of which is the performance of qualified employees. Human resources contribute to the charge of corporate goals. By this, it is important for companies to improve and manage their human resources as well as possible. This study aims to determine how the influence of incentives, task complexity, and company internal control on employee performance. The research method is to use literature review analysis. Our findings show that providing stimulation to employees has a positive effect on employee performance, task difficulty has a significant effect on employee performance, and the company's internal control has a positive effect on employee performance.